Pengaruh Kualitas Produk dan Brand terhadap Loyalitas Konsumen (Studi pada Konsumen Pengguna Produk “Tupperware” di Kelurahan Bandar Buat Padang) - Febsri Susanti; Windy Kusumahati (JURNAL PUNDI, 2020)
Along with social and economic progress, there have been increasing demands in various aspects of life. Therefore, producers must be able to keep pace with changing circumstances to gain consumer loyalty in order to thrive and succeed in the existing market share. The aim of this study is to determine the effect of product quality and branding strategy on consumer loyalty. The population used in this study was residents of Bandar Buat village, Padang who used Tupperware products. The sample is comprised of 85 people. The data was processed using the SPSS program. The results show that product quality and branding has strong influence on consumer loyalty which means that if the products are of high quality and the brand is associated with a positive image, the consumer will be more loyal to an item despite the existence of a number of rival products. Keywords: product quality, brand, customer loyalty.